2018
DOI: 10.1021/acs.analchem.8b03416
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Initiated-Reversible-Addition–Fragmentation-Chain-Transfer Polymerization for Electrochemical DNA Biosensing

Abstract: Sensitive detection of biomolecules is integral for biomarker screening and early diagnosis. Herein, surface-initiated reversible-addition–fragmentation-chain-transfer (SI-RAFT) polymerization is exploited as a novel amplification strategy for highly sensitive electrochemical biosensing of DNA. Briefly, thiol-terminated peptide nucleic acid (PNA) probes are first self-assembled onto a gold electrode for the specific capture of target-DNA fragments; the carboxyl-group-containing dithiobenzoate 4-cyano-4-(phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…In some cases, post-modification time is much longer than actual polymerization time as in AGET ATRP-based electrochemical biodetection, 34,35,38 where electroactive molecules are coupled to the generated polymer. Recent advances [41][42][43]63,64,68 demonstrate the use of electroactive monomers such as FMMA to reduce the amplification time.…”
Section: Comparison Of Polymerizationbased Biodetection Methods and Future Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, post-modification time is much longer than actual polymerization time as in AGET ATRP-based electrochemical biodetection, 34,35,38 where electroactive molecules are coupled to the generated polymer. Recent advances [41][42][43]63,64,68 demonstrate the use of electroactive monomers such as FMMA to reduce the amplification time.…”
Section: Comparison Of Polymerizationbased Biodetection Methods and Future Goalsmentioning
confidence: 99%
“…In addition to enabling visual biodetection, thermally initiated RAFT polymerization has been proposed as an alternative signal amplification strategy to ATRP for electrochemical biosensors. 63,64 RAFT can reduce background signals from non-specific deposition of transition metals on electrodes, which may interfere with electrochemical measurements. Niu and coworkers demonstrated that thermally initiated RAFT polymerization could be exploited as a novel signal- amplifying tool for sensitive electrochemical detection of DNA (Fig.…”
Section: Thermally Initiated Raft Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the utilization of Cu 2+ ions as catalysts may interfere with the next electrochemical experiments because of the non-specific interaction with nucleic acids and the electrochemical deposition of metal on the electrode. For this consideration, they further explored novel surface-initiated electrochemically controlled reversible-addition-fragmentation-chain-transfer (SI-eRAFT) polymerization without the use of transition metal ions for assays [90][91][92]. For instance, they reported a signal-amplified electrochemical sensing of thrombin activity by SI-eRAFT polymerization [93].…”
Section: In Situ Assembly Of Small Molecules and Biomoleculesmentioning
confidence: 99%
“…26,27 Kong and co-workers have proposed various kinds of electrochemical sensor based on RAFT polymerization or ATRP polymerization for detection of sequence-specific DNAs and suggested that RAFT has better bio-compatibility as transition-metal, Cu 2+ of ATRP can cause toxicity. 28,29 Because RAFT polymerization is harmless to biomolecules 30 , it has great application prospects as a simple and effective signal amplification technique for biosensing for biomolecule detection. However, fluorescence detection DNA based on RAFT polymerization signal amplification has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%